The Interaction of Central Nervous System and Acute Kidney Injury: Pathophysiology and Clinical Perspectives - Wang, Yiru; Liu, Siyang; Liu, Qingquan; Lv, Yongman (Frontiers in Physiology, 2022)
Acute kidney injury (AKI) is a common disorder in critically ill hospitalised patients. Its main pathological feature is the activation of the sympathetic nervous system and the renin-angiotensin system (RAS), which is connected with high fatality rate. There is no specific treatment available, and only renal replacement therapy and supportive care can be used to mitigate the effects of the disease, but there is no significant effect on reducing mortality. This review focuses on a generalization of the interaction between acute kidney injury and the central nervous system (CNS), and summarizes the adjustments in the CNS mechanism due to AKI: the CNS further contributes to kidney injury by regulating sympathetic outflow and oxidative stress due to activation of the RAS, as well as increased pro-inflammatory factors. And experimental studies have suggested that inhibiting sympathetic activity and RAS activation in the CNS and blocking oxidative stress can effectively reduce kidney injury caused by AKI. Therefore, it is of significant interest to clarify the mechanism of action between CNS and AKI and use it as a target for clinical interventions to further reduce the mortality and complications of AKI.